Urachal sinus in a 40-year-old male: A case report (Indian Journal of Case Reports, 2020)
The urachus or median umbilical ligament is a normal embryonic remnant of the primitive bladder dome and extends upward from the anterior dome of the bladder toward the umbilicus. The tubular urachus is normally changed into a fibrous band after birth. If this regression is incomplete, disorders of the urachus can appear. Umbilical-urachal sinus occurs when the umbilical end of the urachus fails to obliterate and persists as a fusiform outpouching structure just below the navel. Periumbilical pain and tenderness with a periodic discharge through the navel and a wet umbilicus are usually reported in patients with an umbilical-urachal sinus. We report the case of a 40-year-old, diabetic, and hypertensive male presenting with recurrent episodes of pus discharge from the umbilicus. Further, evaluation with a Computed tomography confirmed the presence of urachal sinus. We discuss the management of the same, along with a brief review of the literature.